An Analysis of 4G Lite Signal Quality on Telkomsel XL Provider and Hutchison 3 Indonesia Using G-Nettrack Pro Application Via Android at State Polytechnic of Sriwijaya - ira, Fakhirah Labibah Amelia; Ali Nurdin; Suroso (Jurnal E-Komtek (Elektro-Komputer-Teknik), 2022)
The use of providers can increase customer satisfaction and the development of various future features. Performing network performance is the main thing that must be considered in network management. Sriwijaya State Polytechnic has several buildings, and many students, lecturers and academic staff. Each individual uses a provider on a mobile phone to communicate. The reason researchers measured the signal quality of Telkomsel, XL and H3I providers using the G-Nettrack Pro application is based on the parameters measured to determine the service's quality. The best RSRP measurement results from XL providers on the first day, with a consequence of -77.5 dBm. The lowest RSRQ value measurement was found on the first day of the H3I provider, with a value of -37.25 dB. The highest SNR value measurement was found on the first day, with a result of 7.56 dB.